2022
DOI: 10.1002/pssa.202100671
|View full text |Cite
|
Sign up to set email alerts
|

Titanium‐Based Vacancy‐Ordered Double Halide Family in Perovskite Solar Cells

Abstract: The toxicity and stability risk of perovskite structured materials have raised concerns in respective to utilization as a solar energy conversion material. The most common perovskite structured material is lead (Pb)-based, which is an element that is knowingly toxic to humans and the environment. Although the stability issue has been well allayed with several optimizations, the ruinous Pb remains a future challenge for perovskite solar cells. Compositional and structural derivatives of the perovskite family, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…It has been stated that Cs 2 TiBr 6 decomposes in air by forming cesium bromide and titanium dioxide [9]. It has also been reported that a final product of CsX (X = Br and Cl) is obtained based on the loss (evaporation) of highly volatile TiX 4 from Cs 2 TiX 6 in the presence of atmospheric oxygen and moisture [12]. In our study, it is seen that Cs 2 TiBr 6 degrades to CsBr according to our XRD results.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…It has been stated that Cs 2 TiBr 6 decomposes in air by forming cesium bromide and titanium dioxide [9]. It has also been reported that a final product of CsX (X = Br and Cl) is obtained based on the loss (evaporation) of highly volatile TiX 4 from Cs 2 TiX 6 in the presence of atmospheric oxygen and moisture [12]. In our study, it is seen that Cs 2 TiBr 6 degrades to CsBr according to our XRD results.…”
Section: Resultssupporting
confidence: 79%
“…Oxygen, humidity, light, and temperature are all unfavorable atmospheric conditions that cause the crystal structure of the perovskite material to break down [5]. In the literature, Cs 2 TiBr 6 were obtained by solutionbased, mechanochemical ball milling, evaporation methods (by exposing the CsBr layer to TiBr 4 vapor), and high-temperature melting [5][6][7][8][9][10][11][12]. It has been reported that the surface degradation of Cs 2 TiBr 6 thin films exposed to air occurs within a short time [6].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an element with high reserves on the earth, titanium has the advantages of non-toxic, harmless, strong corrosion resistance, and good thermal stability [10]. Experimental results show that inorganic lead-free Ti-based halide perovskite has several ideal combinations of properties, including suitable band gaps, excellent optical absorber, positive defect characteristics, and high stability [11]. In addition, such materials exhibit a combination of tetravalent cations and vacancies, creating a 'vacancy ordered' double perovskite structure with adjustable band gaps.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, syngas is a combination of hydrogen and carbon monoxide that is used in a variety of petrochemical and metallurgical processes such as the production of methanol or oxo-chemicals. Syngas is used as a varied feedstock in the Fischer-Tropsch process, which is used to produce methanol and hydrocarbons [3]- [5].…”
Section: Introductionmentioning
confidence: 99%